2013
DOI: 10.1089/dna.2012.1886
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Interaction of Plant Alkaloid Vincristine with DNA and Chromatin: Spectroscopic Study

Abstract: Chromatin has been successfully used as a tool for the study of genome function in cancers. Vincristine as a vinca alkaloid anticancer drug exerts its action by binding to tubulins. In this study the effect of vincristine on DNA and chromatin was investigated employing various spectroscopy techniques as well as thermal denaturation, equilibrium dialysis and DNA-cellulose affinity. The results showed that the binding of vincristine to DNA and chromatin reduced absorbance at both 260 and 210 nm with different ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…Estimation of free energy changes represents exergonic and spontaneous reaction as G is −2.78 and −3.29 kcal/mol for the binding of TPT to DNA and chromatin respectively ( Table 1). The result is in contrast to the binding of anthracycline anticancer drugs to chromatin and DNA in which they prefer naked DNA rather than nucleoprotein structure of chromatin [24,29] but the finding is in agreement with the interaction of anticancer drugs, mitoxantrone [30] and vinca alkaloids such as vinorelbine and vincristine with chromatin [31,32] in which exhibit higher affinity to chromatin than to DNA.…”
Section: Discussionsupporting
confidence: 52%
“…Estimation of free energy changes represents exergonic and spontaneous reaction as G is −2.78 and −3.29 kcal/mol for the binding of TPT to DNA and chromatin respectively ( Table 1). The result is in contrast to the binding of anthracycline anticancer drugs to chromatin and DNA in which they prefer naked DNA rather than nucleoprotein structure of chromatin [24,29] but the finding is in agreement with the interaction of anticancer drugs, mitoxantrone [30] and vinca alkaloids such as vinorelbine and vincristine with chromatin [31,32] in which exhibit higher affinity to chromatin than to DNA.…”
Section: Discussionsupporting
confidence: 52%
“…The studies of Cisp and Vinc demonstrate that a drug can have different modes of action, dependent on dose, [18,49,73,74], and, indeed this is also demonstrated by the time evolution of the cellular DOX accumulation. Therefore, the characteristic spectroscopic signatures will vary as a function of dose, and exposure time, as also demonstrated by Moritz et al [33], Schie et al [34] and Guo et al [35], for DOX exposure, albeit with different cell lines, doses and exposure times.…”
Section: Raman Microspectroscopy For Chemotherapeutic Pre-clinical mentioning
confidence: 99%
“…2 and 3). Previously, it was reported that VCR binds to DNA and chromatina on cancer cells (Mohammadgholi et al, 2013), according to this, the increase in the size of the nucleus could be related with the nuclear envelope disruption which allows vincristine, and perhaps components of chloroformic fractions, enter the nucleus. Another hypothesis is the induction of mitotic catastrophe, because it is known that different classes of cytotoxic agents can induce an abnormal mitosis that results in cell death (Mansilla et al, 2006), given by factors such as abnormal nuclei, nucleus enlarging, multipolar mitoses, or multiple nuclei, characteristic of mitotic catastrophe (Maskey et al, 2013), as it was observed in this study.…”
Section: Resultsmentioning
confidence: 92%